2020
DOI: 10.33328/ejme.2020.005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness of Metabolic Inborn Errors among Male and Female Students at King Abdulaziz University – Rabigh.

Abstract: Context: Inborn errors of metabolism are a large group of rare genetic diseases. The incidence of inborn metabolic errors, collectively, as high as 1 in 2500 live births, but it varies greatly and depends on the population. Presentation is usually in the neonatal period or infancy but can occur at any time. Diagnosis does not require extensive knowledge of biochemical pathways or individual metabolic diseases. Aims: To assess the students’ knowledge about IEM and to plan future improvement in the curriculum if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…This present study discovered an overall insufficiency of IEM-related knowledge among healthcare students, especially in terms of diagnoses, management, and organisational issues of IEMs. These findings were similar to that of a recent Saudi Arabian study which concluded that both medical and non-medical students lacked the knowledge with which to diagnose and manage IEMs (22). This was also consistent with the findings of several other studies, which reported that the majority of healthcare students also lacked knowledge on the organizational issues of rare disorders, * p < 0.05 -significant using Independent t-test for comparison between 2 groups and one-way ANOVA for comparison between three groups.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This present study discovered an overall insufficiency of IEM-related knowledge among healthcare students, especially in terms of diagnoses, management, and organisational issues of IEMs. These findings were similar to that of a recent Saudi Arabian study which concluded that both medical and non-medical students lacked the knowledge with which to diagnose and manage IEMs (22). This was also consistent with the findings of several other studies, which reported that the majority of healthcare students also lacked knowledge on the organizational issues of rare disorders, * p < 0.05 -significant using Independent t-test for comparison between 2 groups and one-way ANOVA for comparison between three groups.…”
Section: Discussionsupporting
confidence: 90%
“…A self-administered questionnaire that consisted of four sections and 47 items was adapted from extant literature (19,22) (Supplemental Table S1, http://www.irdrjournal. com/action/getSupplementalData.php?ID=111).…”
Section: Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…It has been determined that studies have been conducted in Malaysia [ 11 ], Saudi Arabia [ 14 ], and Poland [ 15 ] to evaluate IMD knowledge levels in healthcare sciences students, but such a study has not been conducted in Turkey. Although IMDs are common in Turkey, it is known that the courses on IMDs in the health sciences education curriculum of universities that train health professionals are inadequate.…”
Section: Introductionmentioning
confidence: 99%